Amended FRW Metric and Rényi Dark Energy Model - Ali, Sarfraz; Iqbal, Sabir; Khan, Khuram Ali; Moradi, Hamid Reza (Advances in High Energy Physics, 2021)
This article is devoted to exploring the Rényi holographic dark energy model in the theory of Chern-Simons modified gravity. We studied the deceleration parameter, equation of state, and cosmological plane considering the Amended FRW modal. Modified field equations of -gravity theory gave two independent solutions. In the first case, this model provided the transitional change from deceleration to acceleration compatible with collected observational data. However, it supported a decelerating phase of expansion only in the second case. It was noted that the Equation of State advocated the dominance era under the influence of dark energy in the first case and the second predicted the influence of ΛCDM. In both cases, ω<0,ω′<0 voted that the universe is in a freezing region and its cosmic expansion is more rapidly accelerated in the background of Chern-Simons modified gravity.